2017
DOI: 10.1186/s41476-017-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced damage due to scratches in the surface of nonlinear optical crystals KH2PO4 (KDP)

Abstract: Background: Potassium dihydrogen phosphate (KDP, KH 2 PO 4 ) crystal is an important kind of nonlinear optical crystal because of widespread use in high-intensity laser systems. A critical issue in high-intensity lasers is the laser induced damage to dielectrics since the laser fluence that optical components can stand sets an upper limit to operational fluence of laser systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although the light intensity distribution caused by the triangular scratch is more complex and intense than that of the circular scratch due to the existence of manufacturing-induced front surface scratches, the LIEF of scratches is still smaller than that of cracks, which is similar to reference [20]. As shown in Figure 12c, Zhu et al [79] investigated the influence of surface scratches on the incident light intensity of KDP and found that once the brittle cracks appeared on the side of scratches, the LIEF would increase significantly, which also validated the hazards of brittle damage [19].…”
Section: Effects Of Surface Defects On Initial Energy Deposition Of Kdp Crystalmentioning
confidence: 53%
“…Although the light intensity distribution caused by the triangular scratch is more complex and intense than that of the circular scratch due to the existence of manufacturing-induced front surface scratches, the LIEF of scratches is still smaller than that of cracks, which is similar to reference [20]. As shown in Figure 12c, Zhu et al [79] investigated the influence of surface scratches on the incident light intensity of KDP and found that once the brittle cracks appeared on the side of scratches, the LIEF would increase significantly, which also validated the hazards of brittle damage [19].…”
Section: Effects Of Surface Defects On Initial Energy Deposition Of Kdp Crystalmentioning
confidence: 53%
“…The focal distance of the focusing lens used in this work was 2 m and the equivalent laser spot size was 280 μm. More experimental details on the employed instruments and the used parameters can be found in Refs [11,14]. Because the essence of light is an electromagnetic wave, the process of laser irradiation can be considered as the propagation of an electromagnetic wave through micro-milled KDP optics, which conforms to theory of wave optics.…”
Section: Test Of the Optical Performance Of Micro-milled Kdp Opticsmentioning
confidence: 99%
“…After comparing the outcomes of above methods, it is accepted that micro-milling is the most promising method to complete repair work and can be applied in the future engineering mitigation of laser damage growth on largeaperture KDP optics [10,12]. Nevertheless, it is not a simple and readily available task to remove micro-defects effectively and then curb the damage growth of KDP optics because there are many factors having great influences on the repairing results, including the targeted design of repair contours [13,14], the ductile-regime cutting of KDP brittle crystal [15][16][17], the optimization of process parameters [18,19], etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations